KEBIJAKAN DAN STRATEGI PERTAHANAN INDONESIA (Studi Kasus Konfl ik Di Laut Cina Selatan) - E. Estu Prabowo (Jurnal Ketahanan Nasional, 2013)
This paper explained Indonesia policy and strategy defense’s with the South China Sea conflict case study. The data qualitative showed Indonesia defense’s policy and strategy to anticipated South China Sea conflict had not yet well formulated. The defense’s policy and strategy had not yet in the same direction as the foreign country’s policy which gave special attention to the Southeast Asia region’s dynamic, including South China Sea. Therefore the present defense’ strategy and policy had not yet given attention to the South China Sea conflict dynamic. Indonesia defense’s policy and strategy now considered South China Sea’s conflict able to solved with soft power and do not anticipate the hard power use which would affect the Indonesia’s national need.Keywords: Policy, Strategy, Indonesia’s Defense, Confl ict, South China Sea.